2010
DOI: 10.1021/la101305z
|View full text |Cite
|
Sign up to set email alerts
|

Lyotropic Liquid Crystalline Self-Assembly in Dispersions of Silver Nanowires and Nanoparticles

Abstract: We report demixed nematic lyotropic liquid crystalline phase formation in dispersions of silver nanowires and spherical nanoparticle aggregates in ethylene glycol and water. This phase is observed in samples in spite of the high density, large aspect ratio, and long relaxation times of the nanowires which have an average length of 6.8 microm. Remarkably, in the biphasic region, the nanowire-rich liquid crystalline phase exhibits a strandlike morphology which has only previously been reported for single-walled … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
32
1

Year Published

2011
2011
2016
2016

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 42 publications
(43 citation statements)
references
References 56 publications
10
32
1
Order By: Relevance
“…The effects of spheres are particularly important given that many novel nanorod synthesis processes tend to create nanospheres as a side product. For instance, Murali et al17 recently demonstrated a novel liquid‐crystalline system of silver nanorods and silver nanoparticles with quantitative measurements for the isotropic/biphasic/liquid‐crystalline transition. The data show a ϕ n value that is substantially lower than the Onsager prediction.…”
Section: Introductionsupporting
confidence: 75%
“…The effects of spheres are particularly important given that many novel nanorod synthesis processes tend to create nanospheres as a side product. For instance, Murali et al17 recently demonstrated a novel liquid‐crystalline system of silver nanorods and silver nanoparticles with quantitative measurements for the isotropic/biphasic/liquid‐crystalline transition. The data show a ϕ n value that is substantially lower than the Onsager prediction.…”
Section: Introductionsupporting
confidence: 75%
“…This behavior is quite similar to that of liquid crystalline polymers, 37−39 SWNT−superacid liquid crystals, 12 and silver nanowire liquid crystals. 5 This behavior is very different from that of isotropic dispersions, 40 where oscillatory transients last a few shear units at most. The silica dispersion data also exhibited the scaling behavior previously reported for liquid crystalline polymers.…”
Section: ■ Experimental Sectionmentioning
confidence: 86%
“…4 Murali et al showed that mixtures of high aspect ratio silver nanowires and nanoparticle aggregates formed demixed nematic liquid crystalline phases in both ethylene glycol and water and highlighted the potential for making aligned films for optoelectronic devices. 5 While these and other works have increased our understanding of lyotropic nematic inorganic nanocylinder systems, there have been few reports of smectic phase behavior. The ability to produce appreciable quantities of nanocylinders with narrow size distributions is still evolving, and smectic liquid crystalline phase formation has typically been viewed as requiring a very uniform size distribution.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Lyotropic nematic LC phase formation in dispersions of silver nanowires and nanoparticles in ethylene glycol and water has been reported [39]. The silver nanowires and nanoparticles are coated with polyvinylpyrrolidone and their mixtures are dispersed in ethylene glycol and water.…”
Section: Liquid Crystalline Nanorodsmentioning
confidence: 95%